Psychometric properties of the Burnout Inventory for Referees - Maria Regina Ferreira Brandão; Sidónio Serpa; Antonio Rosado; Robert Weinberg (Motriz: Revista de Educacao Fisica, 2014)
The purpose of this study was to assess the psychometric properties of the Burnout Inventory for Referees (BIR) in Portuguese in a sample of professional soccer referees and to explore the nomological validity of the inventory through concurrent validation. The analysis showed a factorial structure of burnout for the referees with one second order factor and three first order factors; physical and emotional exhaustion, reduced sense of accomplishment and sport devaluation. A cross-validation procedure showed that the factor structure was replicable, and the inventory demonstrated internal reliability as well as convergent and discriminant validity. In addition, the study assessed the concurrent validity of the inventory by examining the correlation between the scores of the Burnout Inventory for Referees and the scores of the Profile of Mood States (POMS). The subscales of burnout and total burnout were positively correlated with tension, depression, anger, fatigue and confusion and negatively with vigor, as expected. In conclusion, the Portuguese version of BIR presents good evidence of validity and reliability in the assessment of referees who may be at risk of suffering from burnout.